REFLECTING ELEMENTS IN CLOTHING FOR USER SECURITY, SOLUTIONS IN CLOTHING DESIGN - Mežinska, Silvija; Salmane, Gunta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Aim of the article is to justify the topicality of contemporary decorative functional solutions in clothing design, emphasizing the necessity of using reflective material elements in clothing during the dark time of the day and assessing the reasons for the lack of existing offer for different user groups. The use of laser technologies, as a modern, diversified design resource and environmentally friendly textile processing method. Research methods: theoretical - analysis of literature sources, statistical data, and analogues; empirical - questionnaires and data processing. Study sample: 288 respondents, period – 2017/2018 study year. The research is of practical importance, as it assesses previous studies, statistical data and analyses the habits of pedestrian reflectors use / non-use in Latvia. The availability of laser equipment at the Rezekne Academy of Technologies provides experimental work with different thickness, different fibre fabrics with a carbon dioxide laser system. The treatment of synthetic fibre reflective fabric is performed by laser cutting, determining the best cutting parameters for a particular type of fabric. As a result, the design of the outfit collection is developed, ensuring a decorative and functional tie in the clothing with reflective elements